Reformulation of the Law Enforcement System in the Issuance of Driver's Licenses Through Driving Education Certification - Setiawan, Dwi Nur; Santiago, Faisal (Ridwan Institute, 2025)
A Driver's License (SIM) in Indonesia is proof of the legality of a person's ability to drive whose issuance is strictly regulated by the Indonesian National Police. However, the implementation of administrative requirements in the form of education certificates and driving training as stipulated in Police Regulation Number 5 of 2021 still faces obstacles in the community. This research aims to examine the urgency of testing the law enforcement system in fulfilling these requirements and formulate a more inclusive and applicable system. The method used is a normative juridical approach with the study of documents and regulations as the basis for analysis, accompanied by a review of Lawrence M. Friedman's legal system theory which includes the structure, substance, and culture of the law. The results of the study show that the failure to implement the requirements of the driving training certificate is greatly influenced by the low legal awareness of the community, the high cost of formal education, and the unequal access to accredited driving schools. Therefore, it is necessary to reformulate the law enforcement system through policies that are adaptive to the socio-economic conditions of the community, such as community-based training, gradual stages of training, and incentives for training institutions. This reformulation is expected to be able to encourage increased legal awareness, expand public participation in formal training, and improve traffic safety systemically. In conclusion, the success of law enforcement in the issuance of driver's licenses is highly determined by the synchronization of regulations with the real conditions of the community as well as the support of a strong legal culture.